2006
DOI: 10.1016/j.wavemoti.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear travelling waves on a spiralling liquid jet

Abstract: We describe the nonlinear evolution of a travelling wave disturbance on a spiralling slender inviscid jet which emerges from a rotating orifice neglecting gravity. One-dimensional equations are derived using asymptotic methods and solved numerically. Some results are presented for this nonlinear theory which is rather different from previous linear theories, showing the influence of surface tension and rotation on the breakup of the jets into droplets. Comparison with the experimental results shows good qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Hence, the apparent viscosity does not affect the steady solution at leading order, except in (3.26) and in a correction to p 1 in (3.25) which does not affect the trajectory, velocity, pressure or jet radius at leading order. This confirms the approach adopted in [16,17] and Pȃrȃu et al [22] also showed numerically that viscosity is not important to the trajectory except in very high viscosity liquids. The slender jet approximation in this case results in no shear across the jet at leading order.…”
Section: Asymptotic Form Of the Steady-state Solutionssupporting
confidence: 78%
“…Hence, the apparent viscosity does not affect the steady solution at leading order, except in (3.26) and in a correction to p 1 in (3.25) which does not affect the trajectory, velocity, pressure or jet radius at leading order. This confirms the approach adopted in [16,17] and Pȃrȃu et al [22] also showed numerically that viscosity is not important to the trajectory except in very high viscosity liquids. The slender jet approximation in this case results in no shear across the jet at leading order.…”
Section: Asymptotic Form Of the Steady-state Solutionssupporting
confidence: 78%
“…The downstream boundary conditions for U, R and S are obtained by quadratic extrapolation of last interval mesh points. In this numerical simulation of the evolution of compound jet, our stopping criteria were taken to be the time at which the minimum dimensionless jet radius was 0.05 [14]. Using a value smaller than this, for example, 0.01 will not alter the resulting observations as close to breakup the evolution of the jet, in particular the radius, changes exponentially.…”
Section: Nonlinear Analysismentioning
confidence: 99%